Aeroload Simulation of Interceptor Missile using Fin Load Simulator - Prasad, M.V.K.S.; Sreehari Rao, Patri; Nayak, Jagannath (Defence Science Journal, 2021)
Interceptor missiles are designed to destroy enemy targets in air. Targets can be destroyed either in atmosphere or out of atmosphere. So for Air Defence scenario, a two layer protection system is required with one taking care of exo atmosphere and another endo atmosphere. In this Air Defence scenario, irrespective of target trajectory interceptor should neutralise it. So the control, guidance are to be designed and validated thoroughly with various scenarios of interceptor and target. These interceptors sense the rates from rate gyroscopes and accelerations from accelerometers which are fitted on board the interceptor. The navigation algorithm calculates the interceptor’s position and velocity from these rates and accelerations from time to time. Using these interceptor data and target information received from ground RADAR or on board seeker, guidance calculates accelerations demand and subsequently rate demand. The control algorithm runs in on board mission computer along with guidance. The control algorithm calculates the commanded rate and eventually commanded deflections to the control fins to move towards the target. The fins have to move as per commanded deflections to meet the mission objective of hitting the target. But the load known as aeroload which comes on the control fins during mission, causes control fins not to move as per command. Due to the difference between control command and physical movement of fin, the expected path towards target deviates. This increases the miss distance and also misses the target hit. This aeroload scenario is to be simulated on ground and some feature is to be designed to take care of it during mission. By studying the control system behaviour due to load, the control autopilot is to be automatically tuned to compensate for the loss in commanded deflections. This scenario can be carried out in Hardware-in-Loop simulation (HILS) setup. Mission load conditions can be applied on hardware actuation system in HILS setup and mission performance can be seen and also with different loads and different autopilot tunings.